A comparison and phylogenetic analysis of the pyrenoid ultrastructure of three Oocystis species (Oocystaceae, Trebouxiophyceae, Chlorophyta) - Li, Feng; Huang, Xianghu; Li, Changling (JOURNAL OF ADVANCES IN BIOLOGY, 2014)
The 18S rRNA gene sequences of three Oocystis species were determined and subjected to two different phylogenetic analysis algorithms. Phylogenetic analysis indicated that they all belong to Oocystaceae. However, the three strains were not members of a monophyletic cluster. New evidence that the genus Oocystis is paraphyletic is provided in this work. The pyrenoid ultrastructure of the three strains was studied using transmission electron microscopy (TEM). Different morphologies of pyrenoids can be distinguished as three types. Oocystis sp. had one pyrenoid surrounded by a sheath of starch consisting of four to six starch plates. The pyrenoid matrix was traversed by several tubular thylakoids. O. nephrocytioides contained two pyrenoids, with each pyrenoid being homogenous and surrounded by a thick, ring-like starch sheath. The thylakoids extend the length of the chloroplast but never traverse the pyrenoid matrix. No starch sheath pyrenoid has been found in Oocystis sp. FACHB 1429, which was traversed by two tubular thylakoids. These results suggest that different morphological features of the pyrenoids, including their associated starch sheath, are speciesspecific.